CXCL12/CXCR4 signaling and other recruitment and homing pathways in fracture repair - Yellowley, Clare (Nature Publishing Group, 2013)
Cell recruitment, migration and homing to the fracture site are essential for the inflammatory process, neovascularization, chondrogenesis, osteogenesis and ultimately bone remodeling. Mesenchymal stem cells (MSCs) are required to navigate from local sources such as the periosteum and local bone marrow, and may also be recruited from the circulation and distant bone marrow. While the local recruitment process may involve matrix binding and degradation, systemic recruitment may utilize extravasation, a process used by leukocytes to exit the vasculature. CXCL12 (stromal cell-derived factor-1 (SDF-1)), a member of the CXC family of chemokines, is thought to have an important role in cell migration at the fracture site. However, there are many molecules upregulated in the hematoma and callus that have chemotactic potential not only for inflammatory cells but also for endothelial cells and MSCs. Surprisingly, there is little direct data to support their role in cell homing during bone healing. Current therapeutics for bone regeneration utilize local or systemic stem cell transplantation. More recently, a novel strategy that involves mobilization of large numbers of endogenous stem and progenitor cells from bone marrow into the circulation has been shown to have positive effects on bone healing. A more complete understanding of the molecular mechanisms underlying cell recruitment and homing subsequent to fracture will facilitate the fine-tuning of such strategies for bone.